MATHEMATICAL THINKING PROCESS OF STUDENTS IN SOLVING CONTROVERSIAL MATHEMATICS PROBLEMS BASED ON DECISION-MAKING TYPES - Dewi, Irmawati Liliana Kusuma; Suprayo, Try; Junaedi, Iwan; Cahyono, Adi Nur (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Developing thinking processes requires unusual treatment and stimulation, such as solving controversial mathematical problems. Problem-solving involves various stages of thinking and producing solutions based on decision-making. However, many students do not go through these stages perfectly, resulting in less optimal decision-making. This research aims to describe students' mathematical thinking processes in solving controversial problems based on decision-making types. The study uses a qualitative descriptive method by selecting 33 student subjects and grouping them based on decision-making types: empirical, heuristic, and rational. The grouping is based on scores from a decision-making type questionnaire, then 5 subjects are selected based on decision-making type, ability to answer questions, and mathematical communication. The instruments used in this study include a decision-making type questionnaire and controversial mathematical problems adapted from instruments developed by experts. Data is analyzed in three stages: data reduction, data presentation, and conclusion drawing. Empirical decision type (EM): Only successful up to the stages of generalizing and guessing, with difficulties in the convincing stage. Heuristic decision type (HE): Effective in specializing, generalizing, and guessing in the first problem but only meets two indicators in the convincing stage. Rational decision type (RA): Difficulty in the convincing stage and challenges in meeting the last stage indicators. The results of this study reveal the thinking process for each decision-making type when solving controversial mathematical problems. The thinking process holds significant importance, thus requiring special attention, especially from teachers, in monitoring students' thinking processes in the classroom.Mengembangkan proses berpikir memerlukan perlakuan dan stimulasi yang tidak biasa, seperti memecahkan masalah matematika kontroversial. Pemecahan masalah mencakup berbagai tahap berpikir dan menghasilkan solusi berdasarkan pengambilan keputusan. Namun, banyak siswa tidak menjalani tahapan ini dengan sempurna, sehingga keputusan yang diambil kurang optimal. Penelitian ini bertujuan untuk mendeskripsikan proses berpikir matematis siswa dalam memecahkan masalah kontroversial berdasarkan tipe pengambilan keputusan. Penelitian ini menggunakan metode deskriptif kualitatif dengan memilih 33 siswa siswa dan dikelompokkan berdasarkan tipe pengambilan keputusan, yaitu empiris, heuristik, dan rasional. Pengelompokan tersebut berdasarkan skor pada kuesioner tipe pengambilan keputusan, kemudian dipilih 5 siswa berdasarkan tipe pengambilan keputusan, kemampuan menjawab soal dan komunikasi matematis. Instrumen dalam penelitian ini berupa kuesioner tipe pengambilan keputusan dan soal kontroversial matematis yang merupakan adaptasi dari instrumen yang dikembangkan oleh para ahli. Data dianalisis dalam tiga tahap, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Tipe pengambilan data empiris (EM): Hanya berhasil sampai pada tahap menggeneralisasi dan menduga, kesulitan pada tahap meyakinkan. Tipe pengambilan heuristik (HE): Efektif pada tahap mengkhususkan, menggeneralisasi, dan menduga pada soal pertama, namun hanya memenuhi dua indikator pada tahap meyakinkan. Tipe pengambilan keputusan rasional (RA): Kesulitan pada tahap meyakinkan dan kesulitan dalam memenuhi indikator tahap terakhir. Hasil penelitian ini mengungkapkan proses berpikir untuk setiap tipe pengambilan keputusan ketika menyelesaikan masalah matematika kontroversial. Proses berpikir memiliki arti penting, sehingga memerlukan perhatian khusus, terutama dari guru, dalam memonitor proses berpikir siswa di dalam kelas.